2005
DOI: 10.1086/431231
|View full text |Cite
|
Sign up to set email alerts
|

Microevolutionary Processes Inferred from AFLP and Morphological Variation inHeliconia bihai(Heliconiaceae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences.Heliconia bihai is a highly poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
(88 reference statements)
3
14
0
Order By: Relevance
“…Regarding intra-and interspecific variability, despite the large diversity of types found in the Heliconia species studied, cultivars exhibited high genetic similarity (Figures 1 and 3). High phenotypic and molecular variability has been found in other studies conducted on heliconias by Berry and Kress (1991), Kumar et al (1998), Marques et al (2004), Meléndez-Ackerman et al (2005), and Marouelli et al (2010). This study also indicated that H. psittacorum and the hybrid H. psittacorum x H. spathocircinata do not belong to the Heliconia subgenus, although most of the species analyzed in this study (H. bihai, H. caribaea, H. orthotricha, H. stricta, H. wagneriana, and H. aurea) did; rather, they belonged to the Stenochlamys Baker subgenus, Stenochlamys (Baker) Schum section , and were revealed to be grouped with the Heliconia subgenus (Figure 2).…”
Section: Samplementioning
confidence: 53%
See 1 more Smart Citation
“…Regarding intra-and interspecific variability, despite the large diversity of types found in the Heliconia species studied, cultivars exhibited high genetic similarity (Figures 1 and 3). High phenotypic and molecular variability has been found in other studies conducted on heliconias by Berry and Kress (1991), Kumar et al (1998), Marques et al (2004), Meléndez-Ackerman et al (2005), and Marouelli et al (2010). This study also indicated that H. psittacorum and the hybrid H. psittacorum x H. spathocircinata do not belong to the Heliconia subgenus, although most of the species analyzed in this study (H. bihai, H. caribaea, H. orthotricha, H. stricta, H. wagneriana, and H. aurea) did; rather, they belonged to the Stenochlamys Baker subgenus, Stenochlamys (Baker) Schum section , and were revealed to be grouped with the Heliconia subgenus (Figure 2).…”
Section: Samplementioning
confidence: 53%
“…Both species are native to the Lesser Antilles and have a common pollinator -the hummingbird (Eulampis jugularis). This flower-pollinator association, also called co-evolution, has been determinant in the evolution of the floral morphology of these two species (Temeles et al, 2000;Temeles and Kress, 2003;Yoshioka, 2003;Meléndez-Ackerman et al, 2005;Lagomarsino and Kress, 2007).…”
Section: Samplementioning
confidence: 99%
“…The high SM coefficients within provenances (Table 3) indicate lower genetic variation within provenances than between them. This contrasts with high heterozygosity levels found in most woody perennials in similar AFLP studies (Chalmers et al 1992;Russell et al 1999;Drummond et al 2000;Dutech et al 2002;Belaj et al 2003;Gaudeul et al 2004;Cardoso et al 2005;Meléndez-Ackerman et al 2005;Ellis et al 2006;Mwase et al 2006) which are mainly outcrossing and long-lived (Hamrick et al 1991). The greatest within-provenance genetic diversity was found in the two provenances that were located furthest north (GBL in the Volta Region, Ghana) and south (MBE in South Province, Cameroon).…”
Section: Morphological and Genetic Variation Between Provenancesmentioning
confidence: 85%
“…AFLP has been used in the order Zingiberales for assessment of diversity in banana cultivars (Musaceae) (Venkatachalam et al 2008); Calathea spp. and hybrids (Marantaceae) (Chao et al 2005); Heliconia bihai L. (Heliconiaceae) (Meléndez-Ackerman et al 2005) and Boesenbergia species (Zingiberaceae) (Techaprasan et al 2008). We are not aware of any previous genetic analysis within Thaumatococcus.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, common genetic analyses must assume Hardy–Weinberg equilibrium in the populations for the loci under analysis. To solve this potential problem, we complemented the analyses with different estimators of genetic diversity, such as the Shannon information index ( H ′), that do not rely on the Hardy–Weinberg assumption (Domínguez et al 2005, Meléndez‐Ackerman et al 2005, Abarca et al 2008). Genetic variation was characterized for each population by calculating the percentage of polymorphic loci ( P P ), and genetic diversity by means of the Shannon information index ( H ′) and Nei's expected heterozygosity ( He ).…”
mentioning
confidence: 99%